VD_FINDINFO Décision / 2015 / 852 vom 20. November 2015 - VD Tribunal cantonal (2015)
PRINCIPE DE LA CÉLÉRITÉ, DÉTENTION PROVISOIRE, MAJORITÉ{ÂGE}, MINORITÉ{ÂGE} | 212 al. 3 CPP (CH), 221 al. 1 let. a CPP (CH), 221 al. 1 let. c CPP (CH), 222 CPP (CH), 393 CPP (CH), 5 CPP (CH)